Epidemiology of asthma. Issue 3 (June 2016) - Loftus, Patricia A.; Wise, Sarah K.
Abstract : Purpose of review: This article reports the findings of recently published research articles and Centers for Disease Control (CDC) data on the epidemiology of asthma. Numerous otolaryngologic diseases are associated with asthma, such as allergic rhinitis, chronic rhinosinusitis, and obstructive sleep apnea. In addition, asthma causes a significant health burden and its prevalence is increasing. Recent findings: Currently, 8.4% of persons in the United States have asthma as compared with 4.3% of the population worldwide, and both numbers are on the rise. The average annual asthma prevalence is higher in children (9.5%) than adults (7.7%). The prevalence of asthma is higher in black persons than white persons, and the ethnicity most affected is the Puerto Rican population. Asthma prevalence increases with each successive lower poverty level group. There are interesting relationships between asthma and certain otolaryngologic diseases. The impact of asthma on both morbidity and mortality is particularly noteworthy. Summary: The prevalence of asthma is increasing both domestically and globally. The impact is most significant in the minority and lower socioeconomic populations. Future research should work to elucidate the reasons for this increase in asthma and promote better access to care for persons across all ethnic and socioeconomic classes.